Strategi Peningkatan Ekonomi Masyarakat Melalui Pengelolaan Wisata Tamsar 27 di Desa Bengkelang Kec. Bandar Pusaka Kabupaten Aceh Tamiang - Mutiara Mutiara; Mika Ardila; Puti Andiny; Martahadi Martahadi; Safuridar Safuridar (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study is motivated by the tourism potential of Tamsar 27 in Bengkelang Village, Bandar Pusaka Sub-district, Aceh Tamiang Regency, which offers clear river streams, scenic natural landscapes, and a peaceful rural atmosphere, yet has not been optimally managed to improve the local economy. The purpose of this research is to analyze strategies for community-based tourism management to enhance local welfare. The research employs a qualitative descriptive approach, using field observations, interviews, and documentation as data-collection techniques. Data were analyzed through reduction, presentation, and conclusion-drawing stages. The results reveal five main strategies for improving community economy through tourism management at Tamsar 27: (1) improving tourism infrastructure; (2) empowering local communities through training in tourism management and entrepreneurship; (3) diversifying tourism-related businesses such as homestays and local specialty products; (4) optimizing digital promotion; and (5) strengthening partnerships among the village government, village-owned enterprises (BUMDes), and private sectors to ensure sustainable tourism development. The implications of this study demonstrate that applying the principles of community-based tourism and empowerment theory provides an effective foundation for developing sustainable rural tourism destinations while simultaneously enhancing local income and community self-reliance.